2011
DOI: 10.1258/ijsa.2011.011174
|View full text |Cite
|
Sign up to set email alerts
|

Non-occupational post-exposure prophylaxis in Victoria, Australia: responding to high rates of re-presentation and low rates of follow-up

Abstract: In Australia, the non-occupational post-exposure prophylaxis service in Victoria (VNPEPS) maintains a database of non-occupational post-exposure prophylaxis (NPEP) use throughout the state. Through the database the service can monitor and respond to patterns of NPEP presentation, re-presentation and follow-up as well as those who test positive for HIV. We describe a cohort of NPEP individuals from the commencement of the service to 31 December 2009. During this time, 1864 individuals presented for NPEP on 2396… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 14 publications
3
25
0
4
Order By: Relevance
“…In surveys conducted among attendees at the Seattle Gay Pride parade (2009–2012) only 26% of attendees were aware of nPEP [unpublished data, Elizabeth Barash]. The majority of studies, with a few exceptions [6], [28], report low demand for nPEP [13], [29][31]. In order to access and benefit from nPEP, individuals must overcome many barriers: 1) recognize an exposure to HIV; 2) be aware of nPEP and where to obtain it; 3) report for care within 72 hours of exposure; 4) have the means to pay for nPEP if they are un- or under-insured and cannot access assistance programs; and 5) preferably know or determine the HIV status of her/his contact.…”
Section: Discussionmentioning
confidence: 99%
“…In surveys conducted among attendees at the Seattle Gay Pride parade (2009–2012) only 26% of attendees were aware of nPEP [unpublished data, Elizabeth Barash]. The majority of studies, with a few exceptions [6], [28], report low demand for nPEP [13], [29][31]. In order to access and benefit from nPEP, individuals must overcome many barriers: 1) recognize an exposure to HIV; 2) be aware of nPEP and where to obtain it; 3) report for care within 72 hours of exposure; 4) have the means to pay for nPEP if they are un- or under-insured and cannot access assistance programs; and 5) preferably know or determine the HIV status of her/his contact.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of an Australian database of PEP prescribing found that repeat presentation for PEPSE occurred in 17.5% of users and that 1.2% of individuals were HIV positive at baseline (392). Higher lifetime and recent sexual risk behaviour was associated with lower adherence to PEPSE in a small study of high risk, methamphetamine using MSM (393).…”
Section: Antiretroviral Post-exposure Prophylaxis For Sexual Exposurementioning
confidence: 96%
“…In effect, PEPsexual as an emergency method has been used more as a complement than as a replacement for other preventive methods 9 . Approximately 80% of the users reported using PEPsexual a single time 88 . Despite being strategic and having a long time of existence, the knowledge about PEPsexual is low among potential users and health professionals.…”
Section: The Last Option Of Prevention For Non-infected People: Post-mentioning
confidence: 99%